(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2018)
The main aim of this article is the diagnosis of the competition on the concrete market and prefabricated concrete market based on maps of strategic groups. As a result of this method is the analysis and assessment of the competition distribution on market and the main competitors specific positions in the particular strategic groups in the sector. It was attempted to systematize of knowledge about the main groups of producers in sector and to identify main competitors. In article the analysis of strategic groups was used as a very useful method to apply in assessment of competition inside sector. Data from the study of internal documentation and interviews in the company Agrobud were used in the study.